The practices of the prophets of ūlū al āzm in their social life through the Qur'ān and Sunnah عادات أولي العزم من الرسل في حياتهم الاجتماعية من خلال القرآن والسنة - Ananda, Fadhli; Gasmelsid, Saadeldin Mansour; Ahmed Ali, Ahmed El-Mogtaba Bannga (2025)
The Messengers of Ūlū al ‘Azm were distinguished Prophets who held high positions and exerted significant influence in their societies. they shared similar Practices and approaches in addressing challenges in their social lives. Their determination and patience in improving the community is seen in the Qur'an and Sunnah. So this research seeks to uncover the habits of Ūlū al Āzm in their social life and reveal the meanings contained therein based on the verses of the Qur'an and Hadith. This research uses the descriptive method of analysis to look at the habits in social life experienced by the Ūlū al Āzmi prophets. Among the conclusions of this study is that the Apostle Ūlū al Āzm both have noble morals, because the Apostle Ūlū al Āzm applies social values that are guided by Allah Ta'ala, as for the differences in times and social conditions experienced by the Apostle Ūlū al Āzm are different but if there are causes and characteristics that are repeated they will use the same approach in improving and restoring social values in their society, because all social values and the ultimate criteria for good and bad social behavior are rooted in divine revelation